Conductive hydro drying through refractance window drying – An alternative technique for drying of Lactobacillus plantarum (NCIM 2083). Issue 5 (3rd April 2020) - Yoha, K. S.; Moses, J. A.; Anandharamakrishnan, C.
Abstract: The process of drying improves the shelf-life of a range of food products. Considering drying of probiotics, retention of cell viability is challenging, yet crucial. The impact of various drying process on probiotics viability is well documented. This study was aimed to prepare probiotic powders of Lactobacillus plantarum with a suitable combination of prebiotics by refractance window (RW) drying, a variant of the conductive hydro drying technique. Properties of RW dried synbiotic powder were investigated and compared with freeze dried samples. RW dried synbiotic powder showed lesser moisture content, better flowability, and porous flaky structures in its surface morphology. RW dried synbiotics showed acceptable probiotic viability and stability under simulated oral-gastrointestinal conditions. The findings of this study highlight a new approach for commercial production of probiotic powders.